Studies in 3-oxy-assisted 3-aza Cope rearrangements - Gomes, Mário (2002)
On thermolysis appropriately substituted N-silyloxy-N-allyl enamines undergo smooth 3,3-sigmatropic rearrangments to the corresponding N-silyloxy imino ethers.